Pembangunan Infrasturktur Big Data Berbasis Hadoop pada Universitas Jambi - Hana, Maryetta; Marzal, Jefri; Mauladi, Mauladi (JUSS (Jurnal Sains dan Sistem Informasi), 2018)
Rapid and diverse data growth is a challenge for managing data. Big Data is a technology that enables data management with 3V characteristics (Volume, Variety, Velocity). This study aims to document the process of building a large data infrastructure using the method of PPDIOO. PPDIOO can be easily described as a method of analyzing the development of computer network installations developed by Cisco. Through a series of steps performed using the PPDIOO method, big data systems can be run that are tested by applying the K-Means algorithm method and Reuters-21578 data. Clustering results show that the more nodes are used the clustering process will be faster.